THE IMPORTANCE OF COMMUNICATIVE STRATEGY IN TEACHING SPEAKING - Zakaria - - (HOLISTICS, 2009)
This paper was written to find out what aspect should be used by a teacher in communicative strategy in teaching  speaking. The aspects consist of grammatical competence, socio linguistic competence and strategic competence. Grammatical competence is an ability to produce and to understand correct syntactic, lexical and phonological forms of a language, socio-linguistic  competence means the use of language context and strategic competence is an ability to transmit information t the listeners. Theoretically, these three aspects show that they cannot be separated from one another in teaching speaking, since they are integrated to each other in communicative strategy. Therefore, it is suggested that the implementation of three aspects be done by a teacher in achieving the main objective of teaching.